Short and Improved Synthesis of Cytotoxic Homodimers with an Isoquinoline Structure - Segura-Segura, R; Segura-Segura, R; Ibacache-Rojas, J; Faundes-Anazco, J (Syscom 18 SRL, 2020)
The syntheses of cytotoxic homodimers 5, 7-10 are described. Compounds 5, 7-10 were cleanly and efficiently obtained by microwave activation. A thorough study concerning oxidative reaction of diamines and isoquinolinequinones, under ultrasound (US) and microwave (MW) irradiation is presented. Under MW irradiation the yields are higher, the amount of precursor quinone used decreases substantially, the reaction time decreases considerably (from hours to minutes) in respect to previously reported methodology. © 2020 SYSCOM 18 S.R.L.. All rights reserved.